Fiqh Contents within a Sufi Book: An Intertextual Study on Kiai Zainullah’s Qurra al-Aṣfiyā’ - Hilal, Muhammad (The Institute of Research and Service Community IPMAFA Pati, 2024)
This paper aims to explore the discussions of Fiqh within a Sufi book entitled Qurra al-Aṣfiyā’ ‘alā Sharh Hidāya al-Adhkiyā’ by Kiai Zainullah, Malang. Employing qualitative research design, this paper uses intertextual study as its analysis tool. The findings reveal that Kiai Zainullah incorporated four Fiqh topics in his work. These topics are 1) differing views among madhhab imams on the status of basmala, 2) the rulings on beautifying one’s voice when reciting the Qur’an, 3) the ruling on listening to women’s singing voice, and 4) the ruling on marriage versus celibacy in term of uzla. The implication of this research highlights the necessity of exploring the relationship between Fiqh and Sufism, especially the Fiqh discussions within a Sufi treatise, in a more creative framework rather than being solely confined to the paradigm of harmonization and alignment.